Planning education for African development : economic and manpower perspectives - Jolly, Richard; East African Institute of Social Research (Makerere University College) ([Nairobi] : Published for the Makerere Institute of Social Research [by] East African Pub. House, 1969)
This book was originally a doctoral thesis, but a most unusual one, because it incorporates work on which governments have taken decisions on.
Bibliography: p. 160-163.
asm; 21/01/19
Loans
Keywords: Economic development